Angel eyes - Lustbader, Eric Van (New York : Fawcett Columbine, 1991)
Three different individuals--American agent Teri Nunn, out to infiltrate the Medellin drug cartel; Irina Ponomareva, searching for a secret Soviet organization; and an ex-cosmonaut transformed by a space accident--become players in a deadly international game.
Keywords: Science fiction; Heroes and heroines -- Fiction